Reconstructing the Integration between Islam and Wasathiyyah Based Social Science: An Epistemological Approach - Zakiyuddin Baidhawy (Institut Agama Islam Negeri (IAIN) Salatiga, 2021)
Abstract This article is aimed to build bridge between Islamic Science and Modern Western Social Science and offer a wasathiyyah (moderate/median) oriented Social Science building from epistemological point of view. Through philosophical approach, this article suggests that in order to develop integrative social science, philosophers and Muslim scholars must incrementally and systematically formulate comprehensive integrative theory building which includes metatheoretical understanding imperative as the foundation or grand theme of the systematization of social theories. This study identifies that the gap in current modern social science is caused by the micro extremism approach and methodological individualism. Here is the importance and relevance of wasathiyyah (moderate/median) as principle of balance (tawazun) between individual and societal claim in the social life of Muslims. Through this proposal, prophetic paradigm putting forward balance/moderation (wasathiyyah) in developing the framework of integrative Islamic Social Science finds clearer orientation and direction. The next step is to derivate them into social theories and their practical forms.